Conductive education as a method of development of creative abilities of preschool children with disorders of the musculoskeletal apparatus - Alfia V. Moskvina; Svetlana A. Susaeva (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The article describes the implementation of the method of conductive pedagogy in the creative potential of preschool children with disorders of the musculo-skeletal system. The description of methodological principles, with the successful application of which is implemented an individual approach to each child. Explores the concept of creativity, creative activity, creative abilities. Addressed the question of the necessity of physical rehabilitation of preschoolers and their socialization. Marked difficulties in physical and intellectual development of preschool children with disorders of the musculo- skeletal apparatus. Some General basic principles of training and education, as well as pedagogical conditions for the formation of creative personality of preschoolers with disorders of the musculo-skeletal system.